2006
DOI: 10.1002/ps.1144
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of sugarcane elite breeding lines and engineering of stem borer resistance

Abstract: Five elite sugarcane breeding lines were tested for efficiency in embryogenesis and plant regeneration. All of them produced regenerative embryogenic calli but with varied efficiencies. To engineer strongly insect-resistant sugarcanes, the GC content of a truncated cry1Ac gene, which encodes the active region of Cry1Ac insecticidal delta-endotoxin, was increased from the original 37.4 to 47.5% following the sugarcane codon usage pattern. The synthetic cry1Ac gene (s-cry1Ac) was placed under the control of maiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 40 publications
3
41
1
2
Order By: Relevance
“…In our study, friable and embryogenic calli of all 4 cultivars were obtained on media containing 2,4-D; casein was added to enhance embryogenic potential of the callus. Similar studies were reported by Weng et al (2006) and Joyce et al (2010). In several other studies, 2,4-D was found to be mandatory for production of friable and embryogenic calli in sugarcane (Snyman, 2004;Ramanand et al, 2005;Franklin et al, 2006;Basnayake et al, 2011;Nawaz et al, 2013).…”
Section: Discussionsupporting
confidence: 83%
“…In our study, friable and embryogenic calli of all 4 cultivars were obtained on media containing 2,4-D; casein was added to enhance embryogenic potential of the callus. Similar studies were reported by Weng et al (2006) and Joyce et al (2010). In several other studies, 2,4-D was found to be mandatory for production of friable and embryogenic calli in sugarcane (Snyman, 2004;Ramanand et al, 2005;Franklin et al, 2006;Basnayake et al, 2011;Nawaz et al, 2013).…”
Section: Discussionsupporting
confidence: 83%
“…(Falco et al 2000 ) • bar , CaMV 35S , Agrobacterium , Phosphinothricin (5 mg/l), No fi eld trial, Co 92061 and Co 671 (Manickavasagam et al 2004 ) • pat , Maize Ubi-1 , Biolistic, Glufosinate ammonium, No fi eld trial, NCo 310 (Leibbrandt and Snyman 2003 ) Biotic stress tolerance Insect • Sugarcane stem borer: -cry1A(b) , CaMV 35S / nos , Electroporation, GUS, Field trial, Ja60-5 (Arencibia et al 1997(Arencibia et al , 1999 , maize phopshoenolpyruvate carboxylase promoter and pith promoter, Biolistic, Neomycin, Field trial, SP80-1842 and SP80-3280 (Braga et al 2003 ) -cry1A(c) , Maize Ubi-1 / nos , Biolistic, Geneticin (50 mg/l), No fi eld trial, YT79-177 and ROC16 (Weng et al 2006 ) • Sugarcane canegrub, gna or pinII , Maize Ubi-1 / nos , Biolistic, Geneticin, No fi eld trial, Q117 (Nutt et al 1999 Metabolic engineering for other economically important traits such as enhancing sucrose content and using transgenic sugarcane to produce novel and value-added products represent a more recent era of genetic improvement (Table 11.2 ).…”
Section: Historical Perspectivementioning
confidence: 99%
“…This marked a major milestone in sugarcane transformation. Further re fi nements in tissue culture media and explant preparation and improvements in biolistic transfer protocols allowed transformation of sugarcane to become fairly routine in many laboratories (Tables 11.1 and 11.2 ), using easily established target tissues, including embryogenic callus (Bower et al 1996 ;Falco et al 2000 ;Gallo-Meagher and Irvine 1996 ;Gilbert et al 2005 ;Ingelbrecht et al 1999 ;Joyce et al 1998 ;Snyman et al 1996 ;Weng et al 2006 ;Zhang et al 1999 ) and immature leaf roll disk explants (Snyman et al 2000(Snyman et al , 2006 . Agrobacterium -mediated gene transfer was successful in sugarcane for a limited number of varieties and target tissues such as embryogenic calli (Arencibia et al 1998 ;Elliott et al 1998 ) , immature leaf sections (Enríquez-Obregón et al 1997 , and axillary meristems (Manickavasagam et al 2004 ) .…”
Section: Historical Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…A expressão heteróloga de inibidores de proteinase em plantas transgênicas apresenta potencial para o controle de pragas (AUGUSTYNIAK et al, 1997;FALCO et al, 2003;WENG et al, 2006 As informações obtidas constituem uma importante base molecular para o desenvolvimento biotecnológico da cultura, uma vez que esforços direcionados ao melhoramento genético dos híbridos de cana-de-açúcar invariavelmente esbarram na complexidade do seu genoma (VETTORE et al, 2003).…”
Section: Resposta a Estresse Bióticounclassified